Effects of Eucalyptus globulus leaves powder on growth performance, internal organs weights, hematological and biochemical parameters of Isa brown pullets - Aduayi Akue; Lamboni Lare; Essodina Talaki (Journal of Applied Poultry Research, 2024)
SUMMARY: The harmful chickens bacteria impedes poultry production and the antibiotics growth promoters (AGP) used presents a public health problem related to residues in poultry products. In 2006, the world health organization prohibited the use of AGP. Indeed, this study was conducted to evaluate the influence of Eucalyptus globulus leaf powder (EgLP) as a growth promoter in Isa brown pullets. The growth parameters, Internal organs, hematology, and biochemical parameters were evaluated from the 9th to the 20th week. A total of 440 56-day-old Isa brown pullets were randomly allocated to 5 groups, each consisting of 4 replications, with 22 pullets in each replication. Treatments consisted of the control diet (CD) without EgLP and antibiotics, a negative control (group B-), CD with antibiotics and no EgLP, a positive control (group B+), CD + 0.25% of EgLP without antibiotic (group B1), CD with 0.50% of EgLP without antibiotic (group B2), and BD with 1% EgLP without antibiotic (group B3). The study reveled that pullet on 0.5% EgLP had the highest weight, feed intake and body weight gain at the end of the grower phase, as like the batches treated with antibiotics. The biochemical parameters such as Alanine aminotransferase and Aspartate aminotransferase concentration were not affected by EgLP supplementation. For hematological parameters, only the leukocytes number from the negative control pullets was statistically higher. In conclusion, the results of this study showed that 0.5% of EgLP served as a useful replacement for antibiotic in Isa brown pullets in the grower phase.